2012
DOI: 10.4236/jep.2012.34044
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Benthic Foraminiferal Assemblages to Copper Exposure: A Pilot Mesocosm Investigation

Abstract: Controlled experiments, including mesocosms and laboratory cultures, are used to identify a potential specific causeeffect relationship that has been previously inferred in field studies. In this study, a series of mesocosm experiments are carried out to assess the impact of different concentrations of copper on benthic foraminiferal assemblages over time. This pilot investigation documents that Cu contamination has a detrimental effect on foraminifera when compared to original and control samples. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This notion is observed by the non-significant growth decrease of S. orbiculus (porcelaneous shell structure) compared to the Amphistegina species (hyaline shell structure) (Figure 6a). Several laboratory studies have shown a connection between HMs exposure to morphological deformities [20,21,23,32,33]. Additionally, several field studies suggested that miliolid species (porcelaneous shell structure) are more easily affected by environmental stresses, which results in deformed shells [65,66].…”
Section: Figure 6 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is observed by the non-significant growth decrease of S. orbiculus (porcelaneous shell structure) compared to the Amphistegina species (hyaline shell structure) (Figure 6a). Several laboratory studies have shown a connection between HMs exposure to morphological deformities [20,21,23,32,33]. Additionally, several field studies suggested that miliolid species (porcelaneous shell structure) are more easily affected by environmental stresses, which results in deformed shells [65,66].…”
Section: Figure 6 (A)mentioning
confidence: 99%
“…This study was promoted by the recent efforts of using benthic foraminiferal shells' geochemistry as reliable and accessible living data loggers for HMs in seawater. Several laboratory experiments and field studies were set to find the HMs' threshold concentrations and their effect on the foraminifera growth rates and population response [20][21][22][23][24][25][26][27][28], pseudopodia activity [22,24,29], symbionts response [30], cytological and morphological alterations [20,25,[28][29][30][31][32][33][34][35][36] (i.e., their vitality), as well as the partition coefficients of HMs between the foraminifera shell and the ambient seawater [4,21,37,38]. Previous studies have examined the physiological response of different benthic foraminifera species to very extreme conditions of 10-500 µg L −1 (120 days) [31] and 3-11 µg L −1 Cu (82 days) [21], and 0-20 mg L −1 Cd (30 days) [22] that are orders of magnitude higher than its 'typical' ambient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Lead undergoes methylation in the environment; organ-lead species are thought to accumulate more readily than inorganic species (Moore, 1991). The input of copper into marine environment comes from different sources, including mining, smelting, domestic and industrial activities and from algaecides and an antifouling applied to boat hulls (Fabrizio and Coccioni, 2012). Copper is naturally found in rocks, water, and air, being an essential element for plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Foraminiferans are used for environmental monitoring within marginal marine habitats, where low foraminiferal densities have been suggested to indicate anthropogenic stress [1][2][3][4][5][6][7]. However, fluctuations in foraminiferal densities could be linked to seasonal changes, low densities occurring during unfavourable seasons [8,9].…”
mentioning
confidence: 99%